The “ $$B→ Kπ $$ B → K π puzzle”: a new perspective - Adam Szabelski (European Physical Journal C: Particles and Fields)
Abstract A phenomenological analysis based on the published branching fractions and CP asymmetry observables of the $$B→ Kπ $$ B → K π , $$B→ π π $$ B → π π and $$B→ KK$$ B → K K dataset is performed. The amplitude decomposition by the topological diagrams and the SU(3) irreducible representation is used. The result of the global fit can be interpreted as a solution to the “ $$B→ Kπ $$ B → K π puzzle”. The obtained precision enables to test a SU(3)-based sum rule showing $$6σ $$ 6 σ discrepancy with the expectation value in the Standard Model scenario. To improve the obtained results the main effort should concentrate on the $$B^0→ K^0π ^0$$ B 0 → K 0 π 0 measurements.